“Phantom smokers”: Young cigarillo users who do not identify as smokers - Lim, Rock (Drug Alcohol Depend, 2019)
INTRODUCTION: Many young consumers of non-cigarette tobacco products, such as cigarillos, do not identify as smokers. These “phantom smokers” tend to underestimate risks to health and feel little urgency to quit. This study examines the prevalence and characteristics of phantom smoker status among young cigarillo users. METHODS: An online survey was conducted among 14–28 year olds who smoke at least 2 cigarillos per week. Phantom smoker status was determined by a negative response to “Do you consider yourself a smoker?” Other variables included smoking frequency, group smoking and sharing, and confidence in ability to quit. Associations between smoker identity and these variables were tested using chi square, independent samples t-tests and multivariable logistic regression. RESULTS: Of 1,089 respondents, 242 (22%) were identified as phantom smokers. Phantoms smoked half as many cigarillos per week as identified smokers (M=4.75, SD=5.11 vs. M=11.33, SD= 0.88, p<.001) and phantoms were more likely to smoke only when sharing (39.7% vs 21.8%, p<.001). While 59.5% of identified smokers also smoked cigarettes, only 33.5% of phantoms did so (p<.001). Most phantom smokers (83.8%) were unconcerned about addiction. Phantoms also expressed greater confidence in their ability to quit (M=4.40, SD=0.98) than did identified smokers (M=3.72, SD=1.25, p<.001). CONCLUSIONS: Despite regular cigarillo use, over 20% of respondents did not identify as smokers. Cigarillo smoking, along with non-daily and shared use, should be routinely assessed among youth. Phantom smokers’ lack of concern about addiction and high confidence in their ability to quit may render conventional messages about smoking risk ineffective.